Morphometric, Meristic, and Species Identification of Nemacheilus spp in the Sibam River, Pekanbaru, Riau - Uneng Rhahma Sari; Windarti Windarti; Ridwan Manda Putra (Jurnal Perikanan dan Kelautan, 2026)
A type of fish suspected to have morphological characteristics similar to Nemacheilus spp was found in the Sibam River. However, the species has not yet been identified with certainty. This study aims to identify the types of Nemacheilus spp in the Sibam River based on morphometric and meristic characteristics. This study was conducted from September to November 2024. Sampling was conducted six times in the upper reaches of the Sibam River at two-week intervals. The fish samples obtained were then measured for their morphometric characteristics and counted for their meristic characteristics, followed by species identification based on relevant literature. The results showed that 38 Nemacheilus spp were caught, comprising 18 males and 20 females. Morphologically, male fish tended to have more contrasting and brighter body colors than females, which were relatively paler. Among the 24 morphometric characters observed, four characters showed differences between male and female fish, namely the head height (HH) of male fish was relatively shorter than females, the body height (BH) of female fish was higher than males, the distance from the dorsal fin to the caudal fin (DFCF) of males is longer than that of females, and the eye diameter (ED) of males is smaller than that of females. The meristic characteristics of male and female fish show similarities, with fin formulas D.II 6-8, P 9-12, V 6-7, A 4-5, and C 13-16.